SUPERNUMERARY PREMOLARS IN MAXILLA AND CONCRESCENCE OF ROOTS – case report - Srbinoska, Daniela; Trpevska, Vesna; Temelkov, Oliver; Simjanovska, Simona; Cadikovska, Elizabeta (Journal of Morphological Sciences, 2021)
The presence of supernumerary teeth is not uncommon in the general population. Supernumerary teeth (hyperodontia) appear more in permanent dentition. Supernumerary teeth which are in the premolar region occur more often in the mandible with different shape and size. They might occur singly or in multiples, be erupted or impacted. The reason of hyperodontia is still unknown. There are a lot of theories. Various theories have been suggested to explain the etiology of supernumerary teeth in general including both, the genetic theory and environmental factors. Furthermore, it has been suggested that supernumerary premolar teeth belong to a third (postpermanent) series. Proliferation of dental lamina has been implicated. The presence of supernumerary teeth usually is connected with some disease or syndromes. Treatment of hyperodontia depends on the area where supernumerary teeth occur. This article presents a case report of an 11-year-old girl with hyperodontia of the first premolar, erupted palatinally in the left side of maxilla. This is supplemental tooth that looks like the permanent premolar. The orthopantomogram and 3D radiograph showed a big possibility of concrescence of both premolars. To make a definitive diagnosis and a plan for orthodontic treatment, OPG and 3D radiograph were crucial. Keywords : supernumerary teeth, concrescence, OPG, 3D radiograph, orthodontic treatment https://doi.org/10.55302/JMS2142141s